2023
DOI: 10.4149/bll_2023_093
|View full text |Cite
|
Sign up to set email alerts
|

The level of dysbiosis of the oral cavity depends on the type of dental prosthesis of the patient

Abstract: The work was aimed to determine the level of oral dysbiosis of patients depending on the type of prosthetics constructures. MATERIALS AND METHODS: The study involved 48 patients with the presence in the oral cavity of fi xed dentures from 4 to 6 units with a service life of no more than 3 years. The samples of plaque from the vestibular surface of dentures were collected to determine the microorganisms in the gingival plaque. Bacteriological research was carried out by the multiplex polymerase chain reaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…According to literature sources [4], diabetes mellitus is a significant risk factor for the development of inflammatory diseases of the oral cavity. Studies have demonstrated a bidirectional relationship between diabetes mellitus and periodontitis, with more severe periodontal tissue destruction in diabetic patients and poor glycemic control in patients with diabetes and periodontitis [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…According to literature sources [4], diabetes mellitus is a significant risk factor for the development of inflammatory diseases of the oral cavity. Studies have demonstrated a bidirectional relationship between diabetes mellitus and periodontitis, with more severe periodontal tissue destruction in diabetic patients and poor glycemic control in patients with diabetes and periodontitis [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Протимікробні НЧ є перспективною стратегією лікування і попередження інфекцій органів ротової порожнини [13] і можуть бути застосовані в різних галузях стоматології: терапевтичній, хірургічній, ортопедичній [14]. Оскільки відомо, що кількісні показники складу мікробіоти при зубному протезуванні мають значні відмінності та різний рівень дисбактеріозу порожнини рота залежно від типу протезів у роті пацієнтів [15] Втрата зубів достатньо поширена і часто лікується встановленням повних або часткових знімних зубних протезів. У ортопедичній стоматології зубні протези мають значний вплив на покращення якості догляду за порожниною рота [16].…”
unclassified